An Integrated AHP–TOPSIS Model for Evaluating and Selecting Ship Docking Material Suppliers (Case Study: PT SMKU Tegal) - Dida Diawara Vavanoli; Diana Puspita Sari; Hery Suliantoro (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to determine the priority of criteria and select the best supplier of ship docking materials at PT Samugara Multikarya Utama (PT SMKU) Tegal using the Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The research employs a mixed methods approach, combining quantitative analysis through questionnaires to obtain criteria weights and supplier rankings, and qualitative analysis through interviews and field observations to understand operational conditions and company needs in the procurement process. The results indicate that the top priority in supplier selection is material quality (quality), which is the most crucial factor in supporting production continuity. The second priority is cost, followed by supplier service and reputation, production capacity and reliability, and delivery timeliness, which ranks last. Based on AHP-TOPSIS calculations, the best supplier for ship docking materials is PT Krakatau Posco as the first choice, followed by PT Samugara Multikarya Utama as the second choice, and PT Gunung Ciremai Sejahtera as the third choice. These findings highlight the importance of systematic, evidence-based evaluation of criteria to support efficient and consistent procurement decisions. This study demonstrates that the AHP-TOPSIS method can provide objective and rational supplier recommendations while enhancing the effectiveness of material procurement processes in the shipbuilding industry. Keywords: Supplier Selection, AHP-TOPSIS, Criteria Priority, Ship Docking Materials